Eggshell Powder: Potential Filler in Concrete - Doh, Shu Ing; Chin, Siew Choo (2014)
An investigation of eggshell powder as potential additive to concrete. In this investigation, five different percentages of eggshell powder with respect to cement were added into the concrete mix of Grade 25. The materials used were mainly Portland cement, crushed sandstone, river sand, plasticing accelerator and eggshell powder. From the investigation, all the slump results of eggshell concrete were at medium degree of worakability ranging from 65-75 mm. Eggshell concrete of 10% achieved the highest compressive strength at 42.82 N/mm2 which is 57% higher than the control specimen. There is an increasing trend of flexural strength from 2.36 to 3.50 N/mm2 with the increase of eggshell powder from 0 to 20%. Besides that, the eggshell concrete has shown significant reduction in water absorption and water penetration